Efeito da inclusão da soja em grão na suplementação de novilhas em pastagem tropical - Cabral , Tassiane Nunes (2020)
The objective of this study was to evaluate the effect of the inclusion of soybeans in the supplementation of heifers on their nutritional and productive performance when maintained in pasture of Uruchloa brizanta grass Xaraés. 45 crossbred heifers (½ Nellore x ½ Brahman) were used, with an average age of seven months and an initial average body weight of 182.9 ± 19.2 kg. In order to minimize dietary restrictions in young animals in forage, supplementation allows a greater supply of nutrients, thus promoting a better response of the animal. In this context, there are several energy and protein sources used in forage-based supplementation, among them, fresh soybeans (SG). Where SG stands out for having a lower market value, for not undergoing any type of processing, for its nutritional value, in addition to having a slow release of lipids in the rumen environment, which does not cause the hydrogenation capacity of ruminal microorganisms to be overcome and also due to its high content of unsaturated fatty acids, which in this way favors changes in the carcass profile, such as final subcutaneous fat (GSF) and final rump fat (GGF), which are widely accepted and used by the industry as an indicator of the composition of carcass. . However, care should be taken with supplementation containing SG, due to the influence of this ingredient on fiber digestibility. Supplementation with SG also influences methane emission, decreasing it within the rumen, which causes less impact on the environment, where a greater amount of energy from the diet ends up being available for the average daily gain (GMD), weight gain (GP) and final weight (PF) of the animals. Thus, the supplement supply with SG corresponds positively to animal performance.